Peanut Growth Promotion and Biocontrol of Blight by Sclerotium rolfsii with Rhizosphere Bacterium, Bacillus siamensis YB-1632 - Yinghang Chang; Qianqian Dong; Limei Zhang; Paul H. Goodwin; Wen Xu; Mingcong Xia; Jie Zhang; Runhong Sun; Chao Wu; Kun Wu; Shuxia Xu; Lirong Yang (Agronomy)
A total of 34 strains of bacteria were isolated from peanut rhizosphere soil, and all showed some in vitro inhibition of the pathogen Sclerotium rolfsii in co-culture. Strain YB-1632 produced the highest level of inhibition and also produced relatively high levels of biofilm in culture. Cell-free culture extracts and volatiles from it were also inhibitory to S. rolfsii. Based on 16S rDNA, gyrA, and gyrB sequences, it was identified as Bacillus siamensis. In the greenhouse, seed treatment resulted in a level of control of peanut sclerotium blight (PSB) comparable to that of a standard fungicide seed treatment. In addition to its antifungal activity, YB-1632 could induce disease resistance in peanut seedlings based on increasing peanut defense enzyme activities and gene expression. The priming of defense gene expression against a necrotrophic pathogen is consistent with Induced Systemic Resistance (ISR). In addition, YB-1632 produced enzyme activities in culture associated with root colonization and plant growth promotion. In the greenhouse, it increased peanut seedling growth, indicating the YB-1632 is a plant growth-promoting rhizobacterium (PGPR). In summary, YB-1632 is a promising novel PSB biocontrol agent and PGPR of peanut.